Comparativo de gestão de risco e controle interno entre a Copa do Mundo de 2014 no Brasil e a Copa do Mundo de 2010 na África do Sul - Carvalho, Valdecy Souza (2015)
The main function of internal control and operational risk management in integrated operations is the ability to mitigate losses due to failure, deficiency or inadequacy of internal processes, people and systems or from external events. Based on this concept, this study analyzes the role of internal control and risk management in a comparative case study between the goals proposed by the organization of the 2014 Fifa WC in Brazil and the 2010 Fifa WC in South Africa. From the literature produced on the subject, including the COSO framework I, II and III, Brazilian Federal Audit Court (TCU) and manuals of the Department of Public Management (GesPública), also Brazilian and foreigner authors that discuss the issue, the 2014 WC Transparency Portal among other primary and secondary sources in the case of Brazil; as well as the site of the South African Football Association and other South African official publications, besides Fifa reports, academic papers and publications of specialized media, this research tries to compose an overview of internal control and risks on the investments of the tournament held in the two countries. Among results, it is observed that both mega-events have accomplished in most aspects and in accordance with the priorities of each govern, although the predicted initial values have been underestimated, reaching triple in the case of Brazil and multiplied in South Africa. In both countries, half of the stadiums built or remodeled for the World Cup have being underutilized causing financial prejudice, and many public contracts, especially for urban mobility, have not been finalized, because of poor risk management and inadequate internal control, especially relating human resources, thus resulting additional losses to public funds